English in Southeast Asia: features, policy and language in use - Hashim, A. (John Benjamins Publishing Company, 2012)
This volume provides a first systematic, comprehensive account of English in Southeast Asia (SEA) based on current research by leading scholars in the field. The volume first provides a systematic account of the linguistic features across all sub-varieties found within each country. It also has a section dedicated to the historical context and language planning policies to provide a background to understanding the development of the linguistic features covered in Part I and, finally, the vibrancy of the sociolinguistic and pragmatic realities that govern actual language in use in a wide variety of domains such as the law, education, popular culture, electronic media and actual pragmatic encounters are also given due coverage. This volume also includes an extensive bibliography of works on English in SEA, thus providing a useful and valuable resource for language researchers, linguists, classroom educators, policy makers and anyone interested in the topic of English in SEA or World Englishes as a whole.